MODIFIKASI KONSENTRASI SUKROSA PADA MEDIA PADAT DAN CAIR UNTUK PERTUMBUHAN KALUS TANAMAN SARANG SEMUT (Myrmecodia tuberosa JACK.) SECARA IN VITRO - Sari, Yanti Puspita (Program Studi Biologi FMIPA Universitas Mataram, 2015)
Ant nest plant (Myrmecodia tuberosa Jack.) is a medicinal plant which belongs to Rubiaceae family. Due to its potency as anticancer, ant nest plant tends to exploit. Direct exploitation of ant nest plant from nature might cause decreasing of its nature population. Therefore, the culture of ant nest plant should be done by using tissue culture. The purpose of this research was to determine the optimum effects of sucrose concentration in solid and liquid medium to increase wet weight callus of ant nest plant by using in vitro technique. A completely randomized design (CRD) with four different sucrose concentration, is 30g/L, 60g/L, 90g/L dan 120g/L were used in solid and liquid medium. The results showed that callus treated any sucrose concentrations had crumb textured form and green to yellowish green color. The highest wet weight callus were found on solid (2.12 g) and liquid (2.03 g) medium which were treated with 30 g/L of sucrose. Key words: Myrmecodia tuberose Jack., Sucrose, solid and liquid medium, callus weight